Sales Promotion and Doctors’ Prescribing Decision: A Review of Literature and Implications for the Nepali Pharmaceutical Market - Acharya, Amrita; Hamid, Abu Bakar Abdul; Kaur, Kamaljeet; Khansa, Medjedel; Wahab, Siti Norida (Journal of Advanced Academic Research, 2026)
The pharmaceutical industry operates in a unique environment where doctors, decide medicines for the patients. This makes the doctors main focus of pharmaceutical marketing, especially through sales promotion activities. This review under study explores how various sales promotion strategies affect doctors’ decision to prescribe with especial lessons for Nepali pharmaceutical market. The study uses a literature review method and includes studies published between 2019 to 2025 from local and global context. The findings show that different sales promotion tools such as: branded gifts, free medicine samples, conference sponsorship, continuous medical education programs and financial incentives strongly influence doctors’ decision to prescribe. Expensive promotions like foreign conference sponsorship, travel support have a greater effect on prescribing decision when compared with small gifts items. Research from many countries including Nepal shows that doctors’ who receive such benefits from pharmaceutical company are more likely to prescribe the promoted medicines. Personal interaction with medical representative and relationship based marketing remain the most effective ways to influence prescriptions. However, these activities benefit both pharmaceutical company and the doctors but also create serious ethical concern. Such activities create potential conflict of interest, lack of transparency and risk to the patients’. The review highlights that in Nepal, weak regulatory systems and limited ethical oversight make doctors more vulnerable to promotional pressure. Therefore, stronger policy measures are needed to ensure transparency and accountability in pharmaceutical marketing. Companies should focus on ethical promotion that supports evidence-based prescribing and prioritizes patient welfare. Establishing clear rules, disclosure systems, and professional education on ethical marketing will help create a fair balance between business goals and medical responsibility in Nepal’s growing pharmaceutical sector.